Paul's letter to the Romans: a socio-rhetorical commentary - Witherington, Ben (William B. Eerdmans Publishing Company, 2004)
While Paul's letter to the Romans is the most studied and commented-on document from the biblical period, the major exegetical books on Romans from the nineteenth and twentieth centuries have been overwhelmingly shaped by the Reformed tradition. Through a careful survey of work on Romans by both ancient Church Fathers and modern exegetical scholars, Ben Witherington III here argues that the interpretation of Romans since the Reformation has been far too indebted to - and at key points led astray by - Augustinian readings of the text as filtered through Luther, Calvin, and others. In this first full-scale socio-rhetorical commentary on Romans, Witherington gleans fresh insights from reading the text of Paul's epistle in light of early Jewish theology, the historical situation of Rome in the middle of the first century A.D., and Paul's own rhetorical concerns. Giving serious consideration to the social and rhetorical background of Romans allows readers to hear Paul on his own terms, not just through the various voices of his later interpreters. Witherington's groundbreaking work also features a new, clear translation of the Greek text, and each section of the commentary ends with a brief discussion titled "Bridging the Horizons," which suggests how the ancient text of Romans may speak to us today.